WML WAP APPLICATIONS USING DESIGN AND DATABASE MYSQL - Arief Lukman; Ir. Rafael A. Gafar Ir. Rafael A. Gafar (Jurnal Sistem Informasi, 2002)
WAP applications are developed by the developer-developer and is used by networkoperators (eg: Indosat) and the companies that own mobile phones (eg Ericsson),whose goal is to add a service to its users.As WAP with WML and PHP we already know that it is used to access theinformation in the Internet world through wireless devices (mobile nature) which ofcourse is different from programming for wired devices that use programminglanguages such as HTML, which is meant here is the WAP just one of the systemsthat exist today.PHP language is combined with WML to create dynamic WEB display means canchange at any time coupled with a MYSQL database server which serves toaccommodate all the necessary data to be displayed as an information.